Fracture resistance of resin based and lithium disilicate endocrowns. Which is better? - A systematic review of in-vitro studies - Joshna Beji Vijayakumar; Preethi Varadan; Lakshmi Balaji; Mathan Rajan; Rajeswari Kalaiselvam; Sindhu Saeralaathan; Arathi Ganesh (Medical Journals Sweden, 2021)
Objectives: The primary objective of this systematic review is to compare the fracture resistance of lithium disilicate (LDS)-based endocrowns and resin-based (RB) endocrowns of in-vitro studies, and the secondary objective is to compare their catastrophic failures. Materials and Methods: The review protocol was registered in the P ROSP ERO database (CRD42020166201). A comprehensive literature search was done in PubMed, Cochrane, EBSCOhost and Google Scholar using key terms. Only in-vitro studies that compared fracture resistance of LDS-based endocrowns and indirect RB endocrowns in molars were included. Data extraction, risk of bias assessment and qualitative analysis of the included studies were performed. Results: Five studies were included in this systematic review. The overall risk of bias for the included studies was moderate. Under axial loading, RB endocrowns showed similar fracture resistance when compared with LDS endocrowns. However, they showed better fracture resistance when compared with zirconia reinforced lithium silicate (ZLS) endocrowns. Furthermore, RB endocrowns showed fewer catastrophic failures than LDS-based endocrowns. Conclusions: RB endocrowns have similar or better fracture resistance and fewer catastrophic failures when compared to LDS-based endocrowns.